Influence of the pulsed current pattern on cross-tension strength of spot-welded joint with nugget diameter variation. Development of resistance spot welding with a pulsed current pattern for ultra-high-strength steel sheets. Issue 4 (3rd June 2019) - Taniguchi, Koichi; Matsuda, Hiroshi; Ikeda, Rinsei
ABSTRACT: Advantageous eﬀect on cross-tension strength (CTS) of resistance spot welds by 'pulsed current pattern' has been evaluated assuming nugget diameter variation which unexpectedly causes deterioration of joint strength of ultra-high-strength steel (UHSS) in auto assembly lines. The pulsed current pattern is newly developed resistance spot welding method consisting of the main welding for forming nugget and multiple combinations of short-time cool time and short-time high-current post-heating (pulsed current) to realize the time-eﬀective change in a brittle nugget. For quantitative evaluation of nugget diameter variation and post-heating eﬀects, various welding experiments and numerical simulations are conducted by various main welding currents without or with 1- or 2-time pulsed current using 1180 MPa grade steel sheets. The experimental results clarify 2-time repetitions of pulsed current ensures plug failure and high CTS over 10 kN at a wider range of nugget diameter than without and even with the 1-time pulsed current. Numerical calculation and cross-sectional microstructures suggest that post-heating with too small nugget diameter overheats nugget and partially remelts phosphorus-rich area due to solidifying segregation leading to low CTS, but repetitive-pulsed current can lower peak temperature to appropriate range to avoid deterioration of CTS. Therefore, the pulsed current pattern is expected to realize high-quality joint even when nugget diameter is insuﬃcient due to instability of welding processes.